Topsy-turvy binding of negatively charged homogalacturonan oligosaccharides to galectin-3. (17th August 2020) - Zheng, Yi; Su, Jiyong; Miller, Michelle C; Geng, Jie; Xu, Xuejiao; Zhang, Tao; Mayzel, Maksim; Zhou, Yifa; Mayo, Kevin H; Tai, Guihua
Abstract: Galectin-3 is crucial to many physiological and pathological processes. The generally accepted dogma is that galectins function extracellularly by binding specifically to β(1→4)-galactoside epitopes on cell surface glycoconjugates. Here, we used crystallography and NMR spectroscopy to demonstrate that negatively charged homogalacturonans (HG, linear polysaccharides of α(1→4)-linked-D -galacturonate (GalA)) bind to the galectin-3 carbohydrate recognition domain. The HG carboxylates at the C6 positions in GalA rings mandate that this saccharide bind galectin-3 in an unconventional, "topsy-turvy" orientation that is flipped by about 180 o relative to that of the canonical β-galactoside lactose. In this binding mode, the reducing end GalA β-anomer of HGs takes the position of the nonreducing end galactose residue in lactose. This novel orientation maintains interactions with the conserved tryptophan and seven of the most crucial lactose-binding residues, albeit with different H-bonding interactions. Nevertheless, the HG molecular orientation and new interactions have essentially the same thermodynamic binding parameters as lactose. Overall, our study provides structural details for a new type of galectin–sugar interaction that broadens glycospace for ligand binding to Gal-3 and suggests how the lectin may recognize other negatively charged polysaccharides like glycoaminoglycans (e.g. heparan sulfate) on the cell surface. This discovery impacts on our understanding of galectin-mediated biological function.